Fontes de carboidrato no comportamento ingestivo de novilhos confinados - Silva, Viviane Santos da (2012)
The aim of this study was to evaluate the influence of different sources of carbohydrates (corn, soybean hulls and wheat bran) on ingestive behavior of twenty four steers with initial average of age and weight of 20 months and 330 kg and Charolais or Nellore predominance. The time spent in feeding activities (214min./day) and total rumination (458min./day) weren t influenced by diet carbohydrate sources. The animals in the wheat bran treatment spent less time in total idling (678min.) in relation to the corn (768min./day) and soybean hulls treatment (774min./day). The neutral detergent fiber (NDF) intake was higher for the animals fed with soybean hulls and wheat bran (5.18 and 5.42 kg/day respectively) compared with those who received corn as a carbohydrate source (3.35kg/day), however the non-fibrous carbohydrates intake was higher for this source of carbohydrate (4.29kg/day), intermediate for wheat bran (2.53kg/day) and lower for those in soybean hulls treatment. The steers fed with soybean hulls presented less intake of digestible energy (27.62Mcal/day) in relation to the corn (35. 5 Mcal/day) and wheat bran (33. 25 Mcal/day) treatments. Rumination efficiency of NDF was higher for soybean hulls (11.92g/min.) and wheat bran (10.23g/min.) compared to corn (7.68g/min.). The chewing time per ruminal bolus was lower for soybean hulls (0.88min./bolus) compared to the diets containing corn (0.96min./bolus) and wheat bran (0.95min./bolus). The animals with Charolais predominance presented higher feeding periods (29.41min.) in relation to the steers with Nellore predominance (24.95min.). The sources of carbohydrates tested didn t influence the feeding and total rumination time of the animals. The animals with Nellore predominance remain less time in lying idling, present longer periods of feeding and spend more time in chewing per ruminal bolus.